PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD NEGERI 136 PALEMBANG: PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SD NEGERI 136 PALEMBANG - atik, atik aprilianti; Hetilaniar, Hetilaniar; Nindiati, Dina Sri (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to determine the Scramble learning model on students' learning motivation in the Indonesian Language subject of second grade of State Elementary School 136 Palembang. This research was conducted at State Elementary School 136 Palembang in the 2024/2025 academic year. The type of research used in this study is a quasi-experimental design with a pre-test post-test control group design. The population in this study were all classes II.A and II.B of State Elementary School 136 Palembang. The sampling technique used in this study was purposive sampling, for class II.A as the experimental class and class II.B as the control class. Data collection techniques used in the study were observation and questionnaires. The results of the study obtained from the average value (posttest) of the experimental class 82.19 and the control class 70.46. And for the hypothesis test using the independent sample t-Test, the tcount value = 3.477> ttable = 2.008 was obtained with a significance level (α) of 0.05, so Ha was accepted and H0 was rejected. It can be concluded that "There is an influence of the Scramble learning model on students' learning motivation in the Indonesian language subject of second grade of State Elementary School 136 Palembang.